Fabrikasi Kawat Baja Pagar Berduri Galvanis Diameter 3 mm Kapasitas 100 m/Jam - Muhammad Rizqi Distiawan; Syamsul Hadi; Satria Dwi Wijaya; Mohammad Arif Dzihni Salim; Immanuel Joseph Isgiarno; Rafi Chozy Asshofi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The vulnerability of security in various industrial, agricultural, and infrastructure sectors as well as areas that are not always under supervision is a problem faced. The purpose of fabrication is to obtain galvanized barbed wire fences with a diameter of 3 mm that is rust-resistant. The fabrication method includes: wire drawing through a die (die) from a diameter of 4 mm to 3 mm, passing the wire into molten Zinc at 450oC (hot dip galvanization) for 1 minute, making pieces of wire with sharp barbed ends of 40 mm and 70 mm long, inserting 1 piece of wire barb with a length of 40, and winding 1 piece of wire barb with a length of 70 mm around 3 pieces of wire body at every 15 cm distance of 3.8 turns, passing the barbed wire twist in molten Zinc for 1 minute, rolling the barbed wire, quality and dimension inspection. The fabrication results are in the form of 3 mm diameter galvanized barbed wire fences that are rust-resistant, the total production cost is IDR 11,500/m, and the production process duration is 36 seconds/m which implies that galvanized barbed wire fences can be used for protective fences in various industrial, agricultural, and infrastructure sectors and unsupervised areas.